2020
DOI: 10.3791/60630
|View full text |Cite
|
Sign up to set email alerts
|

A Rapidly Incremented Tethered-Swimming Maximal Protocol for Cardiorespiratory Assessment of Swimmers

Abstract: Incremental exercise testing is the standard means of assessing cardiorespiratory capacity of endurance athletes. While the maximal rate of oxygen consumption is typically used as the criterion measurement in this regard, two metabolic breakpoints that reflect changes in the dynamics of lactate production/consumption as the work rate is increased are perhaps more relevant for endurance athletes from a functional standpoint. Exercise economy, which represents the rate of oxygen consumption relative to performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The load cell was previously calibrated for 100 Hz signal acquisition, with smoothing performed by the manufacturer’s software package (N2000PRO, Cefise ® , São Paulo, Brazil). Swimmers performed the full front crawl style, trying to displace the body forward as strongly as possible (unsuccessfully) for 30 s (e.g., an all-out bout) for the analysis of force (e.g., mean peaks of force in the 30 s, Fmean), following previous recommendations [ 9 , 13 ]. In summary, these authors [ 9 , 13 ] suggested to consider a baseline (e.g., the force required to align the swimmer horizontally in water and extend the rope system with minimal strain, which should be measured just before the onset of the all-out bout) for the measurement of Fmean.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The load cell was previously calibrated for 100 Hz signal acquisition, with smoothing performed by the manufacturer’s software package (N2000PRO, Cefise ® , São Paulo, Brazil). Swimmers performed the full front crawl style, trying to displace the body forward as strongly as possible (unsuccessfully) for 30 s (e.g., an all-out bout) for the analysis of force (e.g., mean peaks of force in the 30 s, Fmean), following previous recommendations [ 9 , 13 ]. In summary, these authors [ 9 , 13 ] suggested to consider a baseline (e.g., the force required to align the swimmer horizontally in water and extend the rope system with minimal strain, which should be measured just before the onset of the all-out bout) for the measurement of Fmean.…”
Section: Methodsmentioning
confidence: 99%
“…Swimmers performed the full front crawl style, trying to displace the body forward as strongly as possible (unsuccessfully) for 30 s (e.g., an all-out bout) for the analysis of force (e.g., mean peaks of force in the 30 s, Fmean), following previous recommendations [ 9 , 13 ]. In summary, these authors [ 9 , 13 ] suggested to consider a baseline (e.g., the force required to align the swimmer horizontally in water and extend the rope system with minimal strain, which should be measured just before the onset of the all-out bout) for the measurement of Fmean. The fractions of Fmean were the WL applied to grade the swimming intensity during each stage of the ITT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous scientific evidence underlined that for strength measurement, tethered swimming is the most specific in-water test [ 28 ] and can be used with the purpose of evaluating the cardiorespiratory capacity of a swimmer [ 29 ], associated with indications that the relationship between the body composition and performance of swimmers has been a source of unceasing interest among scientists, especially in young athletes [ 30 ]. To our best knowledge, no study has analyzed the relationship between regional body composition, force, and aerobic variables determined throughout tethered swimming and performance in different distance swimming trials in well-trained swimmers.…”
Section: Introductionmentioning
confidence: 99%